Is High Altitude an Emergent Occupational Hazard for Primary Malignant Brain Tumors in Young Adults? A Hypothesis - Sharma, Neelam; Purkayastha, Abhishek; Pandya, Tejas (Indian Journal of Medical and Paediatric Oncology, 2019)
Introduction: Brain cancer accounts for approximately 1.4% of all cancers and 2.3% of all cancer-related deaths. Although relatively rare, the associated morbidity and mortality affecting young- and middle-aged individuals has a major bearing on the death-adjusted life years compared to other malignancies. Over the years, we have observed an increase in the incidence of primary malignant brain tumors (PMBTs) in young adults. This observational analysis is to study the prevalence and pattern of brain tumors in young population and find out any occupational correlation. Materials and Methods: The data were obtained from our tertiary care cancer institute's malignant diseases treatment center registry from January 2008 to January 2018. A total of 416 cases of PMBT were included in this study. Results: Our analysis suggested an overall male predominance with most PMBTs occurring at ages of 20–49 years. The glial tumors constituted 94.3% while other histology identified were gliosarcoma (1) gliomatosis cerebri (1), hemangiopericytoma (3), and pineal tumors (3). In our institute, PMBT constituted 1% of all cancers while 2/416 patients had secondary glioblastoma multiforme with 40% showing positivity for O-6-methylguanine-DNA-methyltransferase promoter methylation. Conclusions: Most patients belonged to a very young age group without any significant family history. A probable hypothesis could be excessive cosmic radiation exposure to persons staying at high altitude areas due to occupational exigencies for which in-depth case–control epidemiological studies are required to reach any conclusion.
Keywords: Cosmic radiation; epidemiology; high altitude; primary malignant brain tumor